2020
DOI: 10.34005/akademika.v9i02.819
|View full text |Cite
|
Sign up to set email alerts
|

Development of E-Learning Smart Apps Creator (Sac) Learning Media for Selling Employees on Paid Tv

Abstract: This study aims to develop E-Learning learning media and test the validity of Android-based Smart Apss Creator (SAC) products for transvision sales employees in Jakarta. Using the Research and development method. The development step refers to the Bord & Gall development model. There are 10 steps in the development of Borg & Gall, but this research is limited to 9 steps, namely research and collection of initial information, planning the initial product format development of the initial trial, product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 1 publication
1
9
0
2
Order By: Relevance
“…The result showed that mobile learning is effective to improve student learning outcomes, it is following the research results of Putra et al (2017); Fatmawati (2015); Nugroho (2014); Surahman and Surjono (2017) that the use of android application-based learning media was able to improve learning outcomes. These results are also following the research conducted by (Andrianto et al, 2020;Jannah et al, 2019;Khasanah et al, 2020) that students are more helped to understand the material by using the Smart Apps Creator learning media, so the score of the student test has increased from before to after using the learning media.…”
Section: Cycle IIsupporting
confidence: 86%
See 2 more Smart Citations
“…The result showed that mobile learning is effective to improve student learning outcomes, it is following the research results of Putra et al (2017); Fatmawati (2015); Nugroho (2014); Surahman and Surjono (2017) that the use of android application-based learning media was able to improve learning outcomes. These results are also following the research conducted by (Andrianto et al, 2020;Jannah et al, 2019;Khasanah et al, 2020) that students are more helped to understand the material by using the Smart Apps Creator learning media, so the score of the student test has increased from before to after using the learning media.…”
Section: Cycle IIsupporting
confidence: 86%
“…One of the strategies to improve learning outcomes by using the Smart Apps Creator 3 application. Smart Apps Creator 3 (SAC-3) is a desktop application for creating android and iOS mobile applications without programming code and can generate HTML5 and .exe formats (Khasanah et al, 2020;Rustandi et al, 2020). Smart Apps Creator 3 can be taught to SD, SMP, SMA / SMK students to increase their creativity in managing content and also creating interesting mobile applications (smartappscreator.com) (Cahyati & Suherman, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambar 2 Alasan rendahnya minat baca siswa Modul merupakan seperangkat bahan ajar yang disusun dalam satu unit atau lebih dan harus dikuasai oleh siswa sebelum berlanjut pada unit berikutnya. Penggunaan e-modul pembelajaran diharapkan dapat menumbuhkan minat baca siswa serta ketuntasan belajar siswa dan sebagai salah satu solusi memberantas permasalahan darurat baca di negeri kita yang kian hari kian rendah selain itu media sejenis e-learning dapat dikembangkan untuk meningkatkan hasil belajar (Khasanah et al, 2020).…”
Section: Gambar 1 Prosentase Minat Baca Siswaunclassified
“…For example, the central government provides input on what support can provide so that Islamic boarding schools can increase their competence. Moreover, they can contribute to and improve people's living standards in their regions or positively impact and contribute to the world community [37], [38]. In stage 1, the initial foundation built consistently because this will become the basis for the next process.…”
Section: Data Setmentioning
confidence: 99%